Evaluation of nutritional status in patients with end-stage renal disease in hemodialysis using principal component analysis - Saenz Pardo Reyes, Erika; Housni, Fatima Ezzahra; López-Espinoza, Antonio; Martinez Moreno, Alma Gabriela; Padilla Galindo, Maria del Rocio (Progress in Nutrition, 2020)
The evaluation of nutritional status in patients with end-stage renal disease in hemodialysis is composed of a large number of measurements that complicate their execution. Therefore, the objective of this study is to reduce the number of variables through the principal component analysis (PCA). For this, a PCA was performed with 10 variables of the nutritional diagnosis in patients with hemodialysis: Energy Intake, Protein Intake, IBM,% UBW,% SBW,% MUAC, cAMA,% TCF, HGS and TLC as well as the age of the patients. The results show that PCA matrix with orthogonal rotation Varimex yielded four main components of the evaluation of the nutritional status of renal disease in patients with end-stage hemodialysis, whose value was greater than 0 and explains the 79.91% of the total variance. The first factor was called body composition status, which is composed of cAMA (r = 0.9138), IBM (r = 0.8755),% MUAC (r = 0.8681) and% SBW (r = 0.6238). In the second factor called nutritional risk, a correlation was observed with energy intake (r = -0.8934), protein intake (r = -0.8752) and %TCF (0.5040). The third component called functional status risk is composed of age (r = 0.9022) and HGS (r = 0.8508). The fourth factor, called body composition stability, was correlated with %UBW (r = 0.7456) and %TCF (r = 0.5825). The results of this study will allow reducing the number of variables for the preparation of a nutritional diagnosis in hemodialysis patients. From many to one of the four main components: 1) body composition status, 2) nutritional risk, 3) functional status risk or 4) body composition stability.